Prevalence of bovine mastitis-related pathogens, identified by mass spectrometry in flies (Insecta, Diptera) captured in the milking environment - Bertolini, A. B. [UNESP]; Prado, A. M.; Thyssen, P. J.; de Souza Ribeiro Mioni, M. [UNESP]; de Gouvea, F. L.R. [UNESP]; da Silva Leite, D.; Langoni, H. [UNESP]; de Figueiredo Pantoja, J. C. [UNESP]; Rall, V. M. [UNESP]; Guimarães, F. F. [UNESP]; Joaquim, S. F. [UNESP]; Guerra, S. T. [UNESP]; et al. (Oxford University Press (OUP), 2022)
Diptera (Insecta) are able to transmit approximately 200 pathogenic microorganisms to humans and animals, causing more than 65 diseases, including bovine mastitis, which constitutes a major cause of economic losses in the dairy industry. In this scenario, 217 adult specimens of Diptera were collected from nine farms and identified to the family and/or species level. Of the 11 families recorded, Muscidae was the most prevalent (152 out of 217; 70%). All Diptera specimens were subjected to microbiological culture using conventional and selective media, and isolates were then identified at the species level by mass spectrometry. In total, 275 microorganisms were identified, with a predominance of pathogens related to environmental bovine mastitis (166/275 = 60·4%), that is, Enterococcus species (70/275 = 25·4%) and Escherichia coli (49/275 = 17·8%). Nontraditional agents related to bovine mastitis (called miscellaneous) were detected in 28% (77/275), as well as microorganisms with well-known zoonotic behaviour (e.g. Bacillus cereus). This is study contributes with knowledge of diversity of microorganisms carried by Diptera in the dairy environment, including pathogens associated with environmental and contagious bovine mastitis, and agents with human relevance. To our knowledge, a three-part chromogenic selective medium used to microbial culture of milk on farms was used for the first time to identification of pathogens in Diptera.
Keywords: bovine mastitis; cattle; environmental and contagious mammary infections; MALDI-TOF MS; vector-borne diseases